Population dynamics of Bactrocera spp., and parasitization efficacy of Opius sp. (Hymenoptera: Braconidae) in citrus varieties - YUNITA FERA RAHMAWATI; AMIN SETYO LEKSONO; AKHMAD RIZALI; ZULFAIDAH PENATA GAMA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Rahmawati YF, Leksono AS, Rizali A, Gama ZP. 2024. Population dynamics of Bactrocera spp., and parasitization efficacy of Opius sp. (Hymenoptera: Braconidae) in citrus varieties. Biodiversitas 25: 4350-4359. Citrus crops play an important role in the agricultural sector of Indonesia. However, farmers face major challenges due to the infestations by the fruit fly, Bactrocera spp., which result in significant economic losses. Therefore, this research aimed to identify the periods of fruit fly infestation and evaluate the effectiveness of parasitoids. The population dynamics of Bactrocera spp. and parasitoids were analyzed across four citrus varieties in Malang District from January to December 2023. Bactrocera dorsalis (Hendel, 1912), Bactrocera carambolae Drew & Hancock, 1994, Bactrocera umbrosa (Fabricius, 1805), and Bactrocera cucurbitae (Coquillett, 1899) were identified using pheromone traps and rearing methods. The results showed that B. dorsalis was the dominant species in all citrus varieties, with the highest abundance in siam madu variety. The Duncan Multiple Range Test (DMRT) tested the fluctuation of Bactrocera spp. and the Bray-Curtis Index was used to measure the abundance in each variety, which was then visualized using Non-metric Multidimensional Scaling (NMMS). Meanwhile, Opius sp. exhibited parasitism rates ranging from 13.52 to 69.10% in the four citrus varieties. Environmental factors, variety characteristics, and monoculture influenced fruit fly abundance and parasitoid effectiveness. July was an important period for pest management interventions, as Opius sp. entered an active time to control fruit flies. Understanding the population dynamics of these pests can help predict outbreaks and optimize the timing of control measures using parasitoids.